Interdisciplinary perspectives on the relation between sleep and learning in early development (Advances in child development and behavior, 2021)
Interdisciplinary Perspectives on the Relation between Sleep and Learning in Early Development, Volume 60, the latest release in this ongoing series, focuses on the relationship between sleep and learning for research and practice. Specific chapters cover Sleep, Learning, Memory and Executive Functioning in Infancy and Early Childhood, Newly walking infants' night sleep impacts next day learning and problem solving, The effect of napping and night-time sleep on memory in infants, The contribution of good sleep to working memory in 2- to 4-year-olds: A matter of duration or regulation?, Sleep development in preschool predicts executive functioning in early elementary school, and more.